Spreading of dengue fever in Singapore : a network based study - Zhang, Ke (2019)
There is an approach based on complex network to model the dengue fever transmission network in both time and space scales proposed in this paper. Particularly, 6647 cases of dengue fever in Singapore from 2009-2010 are used to build the disease transmission network to study the propagation characteristics. Firstly, the Knox test was extended to obtain the main temporal and spatial interaction ranges at a distance of 400 m in 1 week and that of 14.3-14.7 km in second week. Secondly, I pair the cases in 3 different conditions to build 3 networks as the study objects, full cases network, space-time proximity transmission (STPT) network and the human daily traveling transmission (HDTT) network. And the last, through the analysis about assortativity and key nodes identification on 3 networks, the transmission characteristics of 3 patterns have been compared and the key area of transmission has been shown. The significant of STPT network is lower than HDTT network, which means the transmission of dengue fever in Singapore depends more on human movement.